(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The digitalization of the global economy has fundamentally disrupted traditional indirect tax frameworks, necessitating a paradigm shift from physical-presence-based taxation to destination-based consumption taxation. This thesis provides an exhaustive analysis of the legal and administrative evolution of Value Added Tax (VAT) systems, with a specific focus on the European Union (EU) and the Organisation for Economic Co-operation and Development (OECD). It critically assesses the transition from the 2021 VAT e-Commerce Package to the landmark adoption of the "VAT in the Digital Age" (ViDA) package in March 2025. Drawing upon the 2025 VAT Gap Report and 2024 revenue statistics, the research evaluates the efficacy of the One-Stop-Shop (OSS) mechanisms and the introduction of mandatory digital reporting requirements. Furthermore, it examines the jurisprudential implications of recent Court of Justice of the European Union (CJEU) decisions, notably Xyrality (2025) and Fenix International (2023), in defining the liability of digital platforms as "deemed suppliers." The paper argues that while administrative modernization—exemplified by the integration of AI, e-invoicing, and the DAC7/DAC8 transparency directives—has significantly enhanced revenue resilience and reduced fraud, it has simultaneously introduced profound compliance burdens and friction with fundamental rights, particularly regarding data privacy and the proportionality of surveillance mechanisms.